2018
DOI: 10.1016/j.radmeas.2018.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Phototransferred TL properties of alumina substrates

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 22 publications
(26 reference statements)
0
1
0
1
Order By: Relevance
“…A photo-transferred TL (PTTL) study has demonstrated the measurement of deep and more stable traps, with detection limits between 100 and 200 mGy, but for large resistors, which are not found in modern smartphones [95].…”
Section: Smd (Resistors Inductors)mentioning
confidence: 99%
“…A photo-transferred TL (PTTL) study has demonstrated the measurement of deep and more stable traps, with detection limits between 100 and 200 mGy, but for large resistors, which are not found in modern smartphones [95].…”
Section: Smd (Resistors Inductors)mentioning
confidence: 99%
“…Amostras de vidro de telefones celulares touchscreen foram avaliadas com relação ao seu sinal PTTL por McKeever e col. [8], após irradiarem o material com uma fonte de 90 Sr+ 90 Y do sistema leitor TL/OSL Risø. Bossin e col. [9] verificaram a resposta PTTL de substratos de Al2O3, com limite de detecção de 100 mGy e resposta supralinear abaixo de 10 Gy, utilizando exposição à luz azul. Gronchi e Caldas [10] estudaram a resposta PTOSL de detectores comerciais de Al2O3:C, da Landauer, após irradiação do material com fonte de 60 Co, tratamento óptico após a irradiação (utilizando duas lâmpadas fluorescentes com intensidade luminosa de 26.000 lux, em intervalos de tempo entre 10 min e 120 min) e iluminação por intervalos de tempo de 5 min a 60 min, utilizando uma lâmpada UV de mercúrio (Hg).…”
Section: Introductionunclassified